Thyrotoxic periodic paralysis - Fariduddin, M; Chowdhury, NA; Abdullah, AB; Karim, MR (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):89-92.The abstract of this article is available on the PubMed website